2016
DOI: 10.1097/ico.0000000000000828
|View full text |Cite
|
Sign up to set email alerts
|

Increased Straylight in Patients With Keratoconjunctivitis Sicca

Abstract: Keratoconjunctivitis sicca leads to increased straylight. However, this increase was not correlated to the amount of surface damage graded with the van Bijsterveld score. Further study on the cornea is necessary to determine the source of the increased straylight. Scleral lenses do not have a noteworthy influence on straylight in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Further, there was no relationship between central SPK and straylight. Recently, van de Wouw et al 17 reported straylight values in patients with severe keratoconjunctivitis sicca using the same straylight meter utilized in our study. According to that study, increased straylight values were observed in patients with keratocon- junctivitis sicca and this increase was not correlated to the amount of corneal epithelial damage graded with the van Bijsterveld's scoring system, 19 which is consistent with both our previous 16 and current studies.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Further, there was no relationship between central SPK and straylight. Recently, van de Wouw et al 17 reported straylight values in patients with severe keratoconjunctivitis sicca using the same straylight meter utilized in our study. According to that study, increased straylight values were observed in patients with keratocon- junctivitis sicca and this increase was not correlated to the amount of corneal epithelial damage graded with the van Bijsterveld's scoring system, 19 which is consistent with both our previous 16 and current studies.…”
Section: Discussionmentioning
confidence: 71%
“…8 Straylight is known to be a cause of disability glare [9][10][11] and corneal pathologic conditions may produce increased straylight. 12 Decreased contrast sensitivity [13][14][15] and increased straylight 16,17 in dry eye has been reported; however, little is known about the effects of ocular surface regularity in the central corneal region on contrast sensitivity and straylight.…”
mentioning
confidence: 99%
“… 14 , 15 , 16 , 17 , 18 Straylight in the various pathological conditions of the cornea have also been investigated previously. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 In hereditary corneal dystrophies, there is variation in the increase in straylight depending on the type of disease. 19 In eyes with central crystalline dystrophy, straylight was markedly increased with relatively well-preserved visual acuity, while in eyes with posterior polymorphous dystrophy, straylight was not increased regardless of impaired visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions of the cornea and conjunctiva may occur, affecting the integrity of the OS 1. Patients with DED may experience foreign body sensation, burning, itching and aching sensations, heavy eyes, fatigued eyes, and a decreased quality of vision, eg, stray light 4. DED may also increase the risk of infections of the OS 5.…”
Section: Introductionmentioning
confidence: 99%